Mecanismo de ação do estrógeno no gene Amphiregulin em células MCF7 e MDA-MB-231 via P13K - Luvizon, Aline Carbonera [UNESP] (2014)
The relevance of estrogen in breast cancer development is well established in the literature. The use of E2 antagonists for ER-positive breast cancer treatment is shown to be important to patients´ survival. Amphiregulin, a multifunctional growth regulator factor that may be induced by estrogen plays a central role in development of mammary glands and organ morphogenesis, is expressed in both normal and cancerous tissues. Clinical studies suggest that amphiregulin also is important in human breast cancer progression and its expression has been associated with aggressive disease. To investigate the mechanism whereby E2 induces AREG expression, MCF-7 and MDA-MB-231 cells were treated for 10 minutes, 30 minutes, 1 hour or 4 hours with vehicle (control) or estrogen (E2) isolated or in association with Fulvestrant (ICI, estrogen receptor inhibitor), Actinomycin D (ACTD, gene transcription inhibitor), Cycloheximide (CHX, protein synthesis inhibitor ) or LY (PI3K inhibitor). The inhibitors were also used alone. mRNA was extracted from the cells by the Trizol method and AREG expression analyzed by qRT-PCR. Treatment of both cell types with E2 increased AREG mRNA expression at all moments. This increase was partially ER-dependent in MCF- 7 cells at 10 minutes, 1 and 4 hours. At 30 min, no binding of E2 to ER was obseved. In MDA-MB-231 cells, the estrogen-induced AREG mRNA was enhanced by two distinct pathways at the moments analyzed and PI3K pathways participated in one of them. Our results showed that E2 was able to induce the AREG expression in breast cancer cell lines in an ER-dependent and -independent manner